2021
DOI: 10.1152/ajprenal.00139.2021
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the mineralocorticoid receptor in aldosterone-dependent and aldosterone-independent regulation of ENaC in the distal nephron

Abstract: The epithelial sodium channel (ENaC) constitutes the rate-limiting step for sodium absorption in the aldosterone-sensitive distal nephron (ASDN) comprising the late distal convoluted tubule (DCT2), the connecting tubule (CNT) and the collecting duct. Previously, we demonstrated that ENaC activity in the DCT2/CNT transition zone is constitutively high and independent of aldosterone, in contrast to its aldosterone dependence in the late CNT and initial cortical collecting duct (CNT/CCD). The mineralocorticoid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
(82 reference statements)
2
27
0
Order By: Relevance
“…17,21 The data also show that both ENaC and NCC are more severely reduced in the KS-MR −/− mice than in AS −/− mice; this likely reflects direct (ENaC) and indirect (NCC) effects, as we and others have shown that both ENaC and NCC must be reduced for the full salt-wasting phenotype. 17,21,32 Together with results showing that amiloride-sensitive sodium currents along the DCT2/CNT are similar in control and AS −/− mice (see Figure 4 and the study by Nesterov et al 10 ), the results suggest an essential homeostatic role for non- aldosterone MR activation in the kidney. If this is true, then mice lacking aldosterone should still respond to MRA with natriuresis.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…17,21 The data also show that both ENaC and NCC are more severely reduced in the KS-MR −/− mice than in AS −/− mice; this likely reflects direct (ENaC) and indirect (NCC) effects, as we and others have shown that both ENaC and NCC must be reduced for the full salt-wasting phenotype. 17,21,32 Together with results showing that amiloride-sensitive sodium currents along the DCT2/CNT are similar in control and AS −/− mice (see Figure 4 and the study by Nesterov et al 10 ), the results suggest an essential homeostatic role for non- aldosterone MR activation in the kidney. If this is true, then mice lacking aldosterone should still respond to MRA with natriuresis.…”
Section: Discussionsupporting
confidence: 75%
“…In support of this, we found differences between nuclear MR intensity along the CCD of control versus AS −/− mice. Nevertheless, the current data indicate that factors other than nuclear trafficking of MRs are required for aldosterone to stimulate ENaC, as ENaC activity along the CCD is highly dependent on aldosterone concentration (see Figure 4 and the studies by Nesterov et al 10,11 and Wu et al 12 ). In contrast, no difference in nuclear trafficking between control and AS −/− mice was noted along the DCT2/CNT, which exhibits aldosterone-independent ENaC activity.…”
Section: Maeoka Almentioning
confidence: 56%
See 3 more Smart Citations